Gingivitis and Correlated Elements Amongst Patients Visiting Dental Care Facility in Rawalpindi: Gingivitis Amongst Patients Visiting Dental Care Facility in Rawalpindi - Bashir, Namrah; Rashid, Fasila; Bilal, Amna; Hassan, Rashid (Pakistan Journal of Health Sciences, 2022)
Gingivitis is one of the commonly known oral diseases globally. Gingival diseases are non- ordinary contamination that embraces an assorted clan of pathological units triggered by numerous etiologic aspects, if left untouched can crack into an added dangerous malady known as periodontitis. Objectives: To evaluate the incidence of gingivitis in patients coming to dental care facility i.e., DentoScope Institute of Advanced Dentistry, Rawalpindi and to learn the level of gingivitis and its related hazard aspects. Methods: This was a cross sectional research carried out to evaluate the level of gingivitis amongst the subjects appearing at DentoScope Institute of Advanced Dentistry Rawalpindi, Pakistan. The time of the research was eight months from January 2022 to August 2022. Non-probability purposive sampling was carried out for the collection of the subjects. Results: 400 patients were observed of which 172 (43%) were females and 228 (57 %) were males. With a total of 141 patients out of 400, the age group from 30 to 39 appears to be the largest amongst all other varieties, followed by the 40 to 49 age group, which had a total of 131 patients. Conclusions: Inflamed gingiva, also commonly known as gingivitis is an avoidable normally happening disease in Pakistan that can be initiated by several various causative issues. Amongst diverse related risk aspects that cause gingivitis, chewing tobacco or tobacco smoking is the most regular one reported